Associative learning: hebbian flies. - Glanzman, D.L. (Current Biology, 2005)
Fruit flies can learn to associate an odor with an aversive stimulus, such as a shock. New findings indicate that disrupting the expression of N-methyl-D-aspartate (NMDA) receptors in flies impairs olfactory conditioning. The findings provide support for a critical role for NMDA receptors in associative learning.